Gradient‐enhanced damage growth modeling of ductile fracture. (1st July 2021) - Larsson, Ragnar; Ertürk, Ahmet S.
Abstract: We present a gradient‐enhanced damage model for ductile fracture modeling, describing the degraded material response coupled to temperature. Continuum thermodynamics is used to represent components of the energy dissipation as induced by the effective material response, thermal effects, and damage evolution. The viscoplastic Johnson‐Cook constitutive model serves as prototype for the effective material. The continuum damage evolution of Lemaitre type is focusing the degradation of the shear response, eventually leading to ductile shear failure. A novel feature is the damage‐driving dissipation rate, allowing for elastic and plastic components separated by a global damage threshold for accumulation of inelastic damage‐driving energy. In the application to a dynamic split‐Hopkinson test and two quasi‐static tensile tests, the gradient damage model is compared with the corresponding local model. For isothermal conditions, the examples show that both damage models exhibit mesh convergent behavior when using the global damage threshold.